2021
DOI: 10.1101/2021.12.14.21267791
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global SARS-CoV-2 seroprevalence: a systematic review and meta-analysis of standardized population-based studies from Jan 2020-May 2022

Abstract: BackgroundCOVID-19 case data underestimates infection and immunity, especially in low- and middle-income countries (LMICs). We meta-analyzed standardized SARS-CoV-2 seroprevalence studies to estimate global seroprevalence.Objectives/MethodsWe conducted a systematic review and meta-analysis, searching MEDLINE, Embase, Web of Science, preprints, and grey literature for SARS-CoV-2 seroprevalence studies aligned with the WHO UNITY protocol published between 2020-01-01 and 2021-10-29. Eligible studies were extracte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
4
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(95 citation statements)
references
References 51 publications
6
84
4
1
Order By: Relevance
“…We observed lower seroprevalence in children 0-9, perhaps attributable to milder infections in this group which are associated with lower antibody titres [47] and school closures which have been common and lengthy in some African countries. [48] In contrast to our global analysis,[9] we did not find lower seroprevalence in adults 60+ years compared to adults 20-29 years. These results may be due to increased intergenerational mixing at the household level, as prior research in Africa has shown that households sharing space with persons ages 60+ may have increased transmission risk [44].…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…We observed lower seroprevalence in children 0-9, perhaps attributable to milder infections in this group which are associated with lower antibody titres [47] and school closures which have been common and lengthy in some African countries. [48] In contrast to our global analysis,[9] we did not find lower seroprevalence in adults 60+ years compared to adults 20-29 years. These results may be due to increased intergenerational mixing at the household level, as prior research in Africa has shown that households sharing space with persons ages 60+ may have increased transmission risk [44].…”
Section: Discussioncontrasting
confidence: 91%
“…[48] In contrast to our global analysis, [9] we did not find lower seroprevalence in adults 60+ years compared to adults 20-29 years. These results may be due to increased intergenerational mixing at the household level, as prior research in Africa has shown that households sharing space with persons ages 60+ may have increased transmission risk [44].…”
Section: Contextcontrasting
confidence: 99%
See 2 more Smart Citations
“…20 Finally, global synthesis and comparison initiatives: where this has been carried out for seroprevalence, these delays have caused limitations in the synthesis that can be done. 3…”
Section: Discussionmentioning
confidence: 99%